1990
DOI: 10.1042/bj2680699
|View full text |Cite
|
Sign up to set email alerts
|

Distinct ryanodine- and inositol 1,4,5-trisphosphate-binding sites in hepatic microsomes

Abstract: A light hepatic microsomal preparation was fractionated by sucrose-density centrifugation into one rough, one intermediate and two smooth fractions. The four fractions were characterized with respect to parameters relevant to Ca2+ sequestration. Ca2(+)-ATPase activity was similar in the rough, intermediate and smooth I fractions, but lower in the smooth II fraction. Ca2+ accumulation was the highest in the smooth I and intermediate fractions. On the other hand, Ca2+ efflux from the rough fraction was several-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 37 publications
(39 reference statements)
1
18
0
Order By: Relevance
“…However, the polarity of the distribution of the fluorescent tag was not examined. In addition, ryanodine-binding sites do not always reflect the location of RyR itself, as evidenced by the fact that hepatocyte microsomes contain ryanodine-binding sites [30,31], yet hepatocytes do not express RyR [15]. In another recent study, immunochemistry was used to examine RyR expression in pancreatic acini, but no labelling was detected [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, the polarity of the distribution of the fluorescent tag was not examined. In addition, ryanodine-binding sites do not always reflect the location of RyR itself, as evidenced by the fact that hepatocyte microsomes contain ryanodine-binding sites [30,31], yet hepatocytes do not express RyR [15]. In another recent study, immunochemistry was used to examine RyR expression in pancreatic acini, but no labelling was detected [8].…”
Section: Discussionmentioning
confidence: 99%
“…The gradual increase in lCa2+Ii induced by exposure to thapsigargin in glial cells is similar to that seen in other cell types (Law et al, 1990;Thastrup et al, 1990), and is consistent with the inhibition of an endoplasmic reticulum Ca' ' -ATPase and subsequent leakage of Ca2 ' from intracellular stores into the cytoplasm. In contrast, studies of brain, hepatic, and skeletal muscle microsomal preparations provide evidence that dantrolene inhibits Ca' ' -induced Ca2+ release but does not affect IPS-mediated Ca2-release (Ohta et al, 1990;Palade et al, 1989;Shoshan-Barmatz et al, 1990). The effect of dantrolene on intracellular Ca" ' release in sympathetic neurons has been reported to require illumination with ultraviolet light in the range of 335-385 nm (Nohmi et al, 1991).…”
Section: + -mentioning
confidence: 99%
“…Dantrolene has also been shown to have effects on brain cell function in vitro, including inhibition of long-term potentiation in hippocampal slices (Obenhaus et al, 1989) and protection against glutamate toxicity in neurons (Frandsen and Schousboe, 1991). Studies using microsomal preparations have shown that dantrolene specifically inhibits Ca'+-induced Ca" release without affecting IP,-mediated Ca2+ release (Ohta et al, 1990;Palade et al, 1989) and inhibits binding of ryanodine but not IP, to intracellular membrane binding sites (Shoshan-Barmatz et al, 1990). Thapsigargin is a specific inhibitor of endoplasmic reticulum CaZt -ATPases, which causes a leakage of Ca'+ from intracellular IP,-sensitive stores (Lytton et al, 1991;Thastrup et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…RyRs are also found in neurons (2,3), exocrine cells (4), smooth muscle cells (5,6), epithelial cells (7), lymphocytes (8), and sea urchin eggs (9). In all of these cells, RyRs play a central role in the regulation of the intracellular free Ca 2ϩ concentration, whose elevation triggers a cascade of events that culminates in muscle contraction, hormone secretion, lymphocyte activation, egg fertilization, etc.…”
mentioning
confidence: 99%